PENGARUH KEPERCAYAAN DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS MATAHARIMALL.COM - AYU LESTARI, NIKEN (Jurnal Ilmu Manajemen (JIM), 2018)
The growth of online stores makes conventional businesses exploring online business. The conventional business operates online stores but also operates offline stores. Matahari Department Store offline store that has been operating for decades launched an e-commerce called MatahariMall. Shopping through online requires confidence sometimes consumers still feel hesitant because they can not touch and feel the goods directly. The use of O2O payment system (Online to Offline) makes it easy for consumers to transact. This study is a conclusive study to analyze and discuss the influence of trust and ease of transaction at MatahariMall site. The sampling technique used a combination technique of judgmental sampling and snowball sampling with sample size of 220 respondents that MatahariMall consumers between 18 to 35 years. They have already made transactions with O2O purchasing system. The results show that there is a significant influence on the trust and ease of purchase transactions online at MatahariMall.com site. Keywords: trust, ease of transaction, purchase decision online